2020
DOI: 10.5194/acp-20-2795-2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tropospheric NO<sub>2</sub> columns from MAX-DOAS retrievals and regional air quality model simulations

Abstract: Multi-axis differential optical absorption spectroscopy (MAX-DOAS) tropospheric NO 2 column retrievals from four European measurement stations are compared to simulations from five regional air quality models which contribute to the European regional ensemble forecasts and reanalyses of the operational Copernicus Atmosphere Monitoring Service (CAMS). Compared to other observational data usually applied for regional model evaluation, MAX-DOAS data are closer to the regional model data in terms of horizontal and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Moreover, even within the actual sensitivity volume, the sensitivity might vary as a function of distance from the telescope. Blechschmidt et al (2020) have previously demonstrated that accounting for vertical sensitivity of MAX-DOAS (via averaging kernels) does not noticeably affect the simulated VCDs, because most of the NO 2 is located within the boundary layer, and the averaging kernel profile has a similar shape as the model NO 2 vertical profiles. Hence, vertical sensitivity was not an issue where most of the NO 2 is located.…”
Section: Vertical Column Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, even within the actual sensitivity volume, the sensitivity might vary as a function of distance from the telescope. Blechschmidt et al (2020) have previously demonstrated that accounting for vertical sensitivity of MAX-DOAS (via averaging kernels) does not noticeably affect the simulated VCDs, because most of the NO 2 is located within the boundary layer, and the averaging kernel profile has a similar shape as the model NO 2 vertical profiles. Hence, vertical sensitivity was not an issue where most of the NO 2 is located.…”
Section: Vertical Column Densitiesmentioning
confidence: 99%
“…Previous studies (e.g. Blechschmidt et al, 2020, andVlemmix et al, 2015) used the optimal estimation-based profile inversion approach, which also requires an a priori estimate of the NO 2 vertical profile and can bias the model evaluation if the assumed a priori profile is similar to that simulated by the model. The averaging kernels (A k ) can be applied on the model partial column (V k ) to calculate the modified VCD (VCD corr ), using the a priori profile V a k according to Eq.…”
Section: Vertical Column Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we use the publicly available TROPOMI offline v1.2 and v1.3 tropospheric NO 2 data for March-April 2019 and for March-April 2020, accessed via the Copernicus Open Access Hub. The algorithm producing these data is described by van Geffen et al 2019and is based on the approach used for processing OMI/Aura NO 2 data within DOMINO (Dutch OMI NO 2 ) and the FP7 Quality Assurance for Essential Climate Variables projects (Boersma et al, 2011(Boersma et al, , 2018. Routine validation is being carried out by the Validation Data Analysis Facility, who also provide the quarterly validation report of the Copernicus Sentinel-5 Precursor Operational Data Products.…”
Section: Tropomi No 2 Observationsmentioning
confidence: 99%
“…In urban areas, industrial and transportation emissions affect the level of pollutants, and human production activities have a certain periodicity. The traffic load on the roads on weekends and the slowdown of industrial activities produce lower pollutant emissions levels [52,53]. Previous studies have shown that there are no significant weekend effects in many major cities in China.…”
Section: Weekly Variationmentioning
confidence: 99%